IN SILICO STRUCTURAL AND FUNCTIONAL ANALYSIS OF WRKY1 AND WRKY3 GENES IN THE SELECTED CEREAL CROPS - M. T. Pervez; M. E. Babar; J. Iqbal; M. J. U. Hasnain; S. H. Abbas; S. S. M. Shah; M. Ashraf (Journal of Animal and Plant Sciences, 2020)
The WRKY family is one of the largest transcription factor families in higher plants and plays an important role in the growth of plants, their development, and response to biotic and abiotic stresses. They have capability to regulate the expression of other genes that enhance tolerance of plants to stress. Several studies have reported genome- wide identification of the WRKY transcription factors in individual crops however, only limited information is available on structural, functional and phylogenetic relationships among WRKY genes that are found in various crops. The proposed study investigated two WRKY genes (WRKY1 and WRKY3) in seven cereal crops namely: Rice (Oryza sativa Japonica), Rice (Oryza sativa Indica), Barley (Hordeum vulgare), Sorghum (Sorghum bicolor), Millet (Setaria italica), Wheat (Triticum aestivum), and Corn or Maize (Zea mays). The required DNA and protein sequences were downloaded from NCBI. The eight types of in-silico investigations were performed using various bioinformatics tools. Multiple sequence alignment was generated using MUSCLE embedded in IVisTMSA, percentage of identity and similarity was calculated using E-SICT, physiochemical property analysis was performed through ProtParam, phylogenetic analysis was carried out using MEGA, MEME was used for motif analysis, InterProScan was used for domain analysis, Gene Structure Display Server 2.0 was used for gene structure analysis. GORIV and Swiss homology modelling server were used for protein 2D/3D structural analysis revealed high degree of divergence among all WRKY proteins. However, SiWRKY1, a WRKY discovered in Millet (Setaria italica)) and ZmWRKY1, and a WRKY found in Maize (Zea mays) showed the highest closeness. Based on the results reported by various computational tools, SiWRKY1 and ZmWRKY1 displayed the closest relationship with similar structure and function. Secondly the findings of the proposed study indicated that the proteins having similar 3D structure will also have similar properties. Thus, the proposed study will be very useful for investigating further aspects of the WRKY genes found in various crops and plants.
Keywords: WRKY transcription factors; In silico study of WRKY genes; Cereal crops; Phylogenetic analysis; Gene structure; Physiochemical properties